Identification of dyes in toned and tinted XX century cinematographic films by surface enhanced Raman spectroscopy. (15th October 2015) - Lofrumento, C.; Prati, S.; Ricci, M.; Bonacini, I.; Quaranta, M.; Sciutto, G.; Ballarin, B.; Cassani, M.C.; Castellucci, E.; Mazzeo, R.
Abstract : In this paper some colored frames coming from the very popular cinematographic film Sardinian Drummer Boy, dating back to the beginning of the XX century, were analyzed. The presence in the emulsion of silver nanoparticles (AgNPs), which are formed thanks to the impression–development mechanism, confers to the cinematographic film the characteristic of being an efficient Surface Enhancement Raman Spectroscopy (SERS) substrate. This peculiarity makes it possible to investigate, in a non‐invasive way, the nature of the film components, such as the dyes used for the coloring process. In particular, Raman analyses allowed the unambiguous identification of the dyes used in tinted frames, i.e. tartrazine and safranin, in which the colorant is absorbed by the gelatin, and in toned frames, i.e. Rhodamine B, where the dye is fixed thanks to the formation of an insoluble species with AgI obtained by conversion of metallic silver. This second case is of particular interest to evaluate the possibility to identify the dye even when it is present as a silver iodide derivative. For this purpose an AgI‐colorant derivative has been prepared and its SERS spectrum compared with that obtained on the film sheet. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Some colored frames from the Sardinian Drummer Boy film, dating back to the beginning of the XX century, were analyzed by micro‐Raman spectroscopy. The presence in the emulsion of AgNPs allows the identification of the dyes used in tinted frames, and in toned frames, where the dye is fixed thanks to the formation of an insoluble species with AgI formed by silver conversion.